Apolipoprotein A-I levels in the survival of patients with colorectal cancer: a retrospective study - Xie, Hailun; Wei, Lishuang; Wang, Qiwen; Tang, Shuangyi; Gan, Jialiang (Frontiers in Endocrinology, 2024)
Background: Abnormal lipid levels have been associated with cancer incidence and progression.However, limited studies have investigated the relationship between apolipoprotein A-I (ApoA-I) and colorectal cancer (CRC). This study assessed the significance of ApoA-I levels in progressionfree survival (PFS) and overall survival (OS) of patients with CRC.Methods: Survival curves were compared using Kaplan-Meier analysis, while the predictive values of various lipid indicators in CRC prognosis were evaluated based on receiver operating characteristic curves. The factors influencing PFS and OS in patients with CRC were analyzed using Cox proportional hazards regression models. Finally, the relationship between ApoA-I level and disease recurrence was investigated through logistic regression analysis. The optimal Apo-I level was determined through maximally selected rank statistics.Results: Using the optimal ApoA-Ⅰ cutoff value (0.9 g/L), the 1,270 patients with CRC were categorized into low (< 0.9 g/L, 275 cases) and high (≥0.9 g/L, 995 cases) ApoA-Ⅰ groups. Compared with other lipid indicators, ApoA-I demonstrated superior predictive accuracy. The high ApoA-I group exhibited significantly higher survival rates than the low ApoA-I group (PFS, 64.8% vs.45.2%, P < 0.001; OS, 66.1% vs. 48.6%, P < 0.001). Each one-standard-deviation increase in ApoA-Ⅰ level was related to a 12.0% decrease in PFS risk (hazard ratio [HR] 0.880; 95% confidence interval [CI], 0.801-0.968; P = 0.009) and an 11.2% decrease in OS risk (HR 0.888; 95%CI, 0.806-0.978; P = 0.015). Logistic regression analysis revealed that patients with low ApoA-Ⅰ had a 32.5% increased risk of disease recurrence (odds ratio [OR] 0.675; 95%CI, 0.481-0.946; P = 0.0225) compared with those with high ApoA-Ⅰ. PFS/OS nomograms based on ApoA-I demonstrated excellent prognostic prediction accuracy.Serum ApoA-I level may be a valuable and non-invasive tool for predicting PFS and OS in patients with CRC.